1995
DOI: 10.1681/asn.v62257
|View full text |Cite
|
Sign up to set email alerts
|

Plasma clearance of nonradioactive iohexol as a measure of glomerular filtration rate.

Abstract: Renal clearance of inulin is the best available indicator of GFR but cannot be used routinely for clinical purposes and is also difficult to perform for clinical investigation when repeated measurements are required. The aim of this study was to find a reliable alternative to inulin clearance that would allow one to avoid the use of radioactivity and problems related to the continuous infusion of the marker. The plasma clearance of unlabeled iohexol, a nonionic contrast agent, was used. Forty-one patients (cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(68 citation statements)
references
References 0 publications
1
64
2
1
Order By: Relevance
“…Analysis of the non-ionic contrast medium iohexol can be performed with several methods: liquid chromatography-tandem mass spectrometry (LC-MS/MS) [8], highperformance liquid chromatography-ultraviolet detection (HPLC-UV) [51,52], and X-ray fluorescence [8]. In an aqueous solution, iohexol exists as a mixture of isomers, which slowly interconvert and gradually equilibrate to an isomeric ratio [53].…”
Section: Non-edematousmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the non-ionic contrast medium iohexol can be performed with several methods: liquid chromatography-tandem mass spectrometry (LC-MS/MS) [8], highperformance liquid chromatography-ultraviolet detection (HPLC-UV) [51,52], and X-ray fluorescence [8]. In an aqueous solution, iohexol exists as a mixture of isomers, which slowly interconvert and gradually equilibrate to an isomeric ratio [53].…”
Section: Non-edematousmentioning
confidence: 99%
“…These differences in the reported plasma iohexol clearances might be explained by divergent registered concentrations by LC-MS/MS vs. HPLC-UV, related to a variable presence of endo-and exo-isomers of iohexol [27]. In the majority of HPLC-UV measurement procedures, separation and quantification are only based on the major (exo-iohexol) isomeric peak [26,51,57]. In contrast to HPLC-UV, LC-MS/MS measurement procedures typically do not separate iohexol isomers and quantify all forms of iohexol in one single integration event.…”
Section: Non-edematousmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in previous studies have suggested that in early stages of ADPKD, the variability in serum creatinine levels may be explained by creatinine production related to muscle mass or protein intake rather than glomerular filtration [ 22 ]. Therefore, direct measurements of GFR by gold-standard techniques depended on the use of exogenous markers such as inulin, iohexol or radio-labeled tracers, which would be essential in order to assess the accuracy of GFR decline in the studied population [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%